A recepção de clássicos da literatura na educação básica: desafios e possibilidades no âmbito da docência - Teles, Suzana Miranda (2022)
This dissertation is the result of the Stricto Sensu Professional Master's Course of the Graduate Program in Teaching in Basic Education, from the Center for Teaching and Research Applied to Education, Federal University of Goiás (PPGEEB-CEPAE-UFG). It presents an investigation about the reception of classics of literature in Basic Education, developed with students of the 8th year of Elementary School of a school of the State Education Network, located in the Midwest of Goiás. This is a research that sought to reflect on the process of reception, by students, of works considered as cultural heritage, as well as on the challenges faced by teachers in the classroom, to promote the reading of classics among young people, especially in the current context, in which there is wide access to Information and Communication Technologies (ICTs). The assumption is that this challenge can be overcome if contexts are created in which barriers to the reception of works are broken, such as those related to historical and linguistic aspects. The research was qualitative and based on theorists who discuss the importance of literary classics in the formation of the reader, such as Calvino (1997), Machado (2009) and Colomer (2017), and about the reader reception, such as Jauss (1979). , 1990) and Iser (1996). As a literary corpus of the field research, Machadian and ―One Thousand and One Nights‖ narratives were selected. Data collection took place from the activities applied during the field research and the analyzes and reflections started from the observation of the involvement of the students participating in the research with the selected texts. The Educational Product consists of a book entitled Literary Classics and Reading Memories consisting of texts produced by students during the research, and is presented in two formats: digital book and printed book. One version will be made available in digital media and the other will be part of the library collection of the research field school. It is hoped that the research carried out will contribute to reflections on the importance of reading literary classics in Basic Education and provide elements to envision possibilities for teaching literature, from the perspective of the formation of young contemporary readers.